Intangible capital as a production factor: Firm-level evidence from Austrian microdata - Klaus S. Friesenbichler; Agnes Kügler; Julia Schieber-Knöbl (Austrian Institute of Economic Research (WIFO), 2023)
We examine the role of intangible capital as a production factor using Austrian firm-level register data. Descriptive statistics show that intangible investment has increased over time. The intensive and extensive margins of firms' investments are highly skewed. They differ across sectors. A series of sample splits show that the components of intangible capital play different roles as inputs in the production function. Software and especially licenses are important for SMEs and exporters. Research and development play an important role in production in all specifications. For firms that continuously invest in intangible capital, all components of intangible capital gain importance in the production functions. These patterns differ from those found in previous studies and have implications for the strategic orientation of industrial and innovation policy.
Keywords: D24; O30; L22; C33; 330; intangible capital; R&D; firm level productivity; investment; production function; Austria